Risk-Based Screening for Thyroid Dysfunction during Pregnancy - Masanao Ohashi; Seishi Furukawa; Kaori Michikata; Katsuhide Kai; Hiroshi Sameshima; Tsuyomu Ikenoue (Journal of Pregnancy)
Objective. We conducted the study to see the incidence of thyroid dysfunction in women with obstetrical high-risk factors. Methods. We retrospectively reviewed medical charts of high-risk pregnant women who had examination for thyroid function during pregnancy. Women were divided according to clinical presentation, symptoms of thyroid disease and those with a personal history of thyroid disease (thyroid disease, n=32), intrauterine growth restriction (IUGR, n=115), diabetes mellitus (diabetes, n=115), hypertension (n=63), intrauterine fetal death (IUFD, n=52), and placental abruption (abruption, n=15). The incidence of thyroid dysfunctions including hyperthyroidism or hypothyroidism was compared. Results. The overall prevalence of thyroid dysfunction was 24.7%. The incidence of thyroid dysfunction in each group was as follows: 31% in thyroid disease, 25% in IUGR, 30% in diabetes, 27% in hypertension, 12% in IUFD, and 7% in abruption. Except IUFD, the incidence was not statistically significant from the group of thyroid disease (thyroid disease versus IUFD, P=0.03 by χ2 test). Thyroid disease represented for only 10% of all thyroid dysfunctions. Conclusion. Testing of women with a personal history or current symptoms of thyroid disease during pregnancy may be insufficient to detect women with thyroid dysfunction, who will become at high-risk pregnancy.